2022
DOI: 10.3390/su141811615
|View full text |Cite
|
Sign up to set email alerts
|

Intellectual Capital History and Trends: A Bibliometric Analysis Using Scopus Database

Abstract: This article aims to provide a bibliometric analysis of intellectual capital research published in the Scopus database from 1956 to 2020 to trace the development of scientific activities that can pave the way for future studies by shedding light on the gaps in the field. The analysis focuses on 638 intellectual capital-related papers published in the Scopus database over 60 years, drawing upon a bibliometric analysis using VOSviewer. This paper highlights the mainstream of the current research in the intellect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 82 publications
0
7
0
Order By: Relevance
“…In-depth research on IC has already been extensively published in the literature. Al-Khoury et al (2022) conducted a study on the history and trends of IC and found that a significant majority of the articles, approximately 89%, originated from developed countries. This disproportionate focus on developed countries has led to a research gap in understanding IC in developing countries, particularly in Africa and other regions.…”
Section: Intellectual Capital Of Manufacturing Firmsmentioning
confidence: 99%
See 1 more Smart Citation
“…In-depth research on IC has already been extensively published in the literature. Al-Khoury et al (2022) conducted a study on the history and trends of IC and found that a significant majority of the articles, approximately 89%, originated from developed countries. This disproportionate focus on developed countries has led to a research gap in understanding IC in developing countries, particularly in Africa and other regions.…”
Section: Intellectual Capital Of Manufacturing Firmsmentioning
confidence: 99%
“…In-depth research on IC has already been extensively published in the literature. Al-Khoury et al. (2022) conducted a study on the history and trends of IC and found that a significant majority of the articles, approximately 89%, originated from developed countries.…”
Section: Introductionmentioning
confidence: 99%
“…To summarize the literature studies on management accounting (Dönmez et al, 2011;Balstad & Berg, 2020), blockchain in accounting (Lardo et al, 2022), sustainability reporting (Pasko et al, 2021), intellectual capital (Al-Khoury et al, 2022), integrated reporting (Doan, 2020), and green accounting (Karcıoğlu & Tosunoğlu, 2022). Furthermore, many studies in the accounting literature in line with the examinations specific to accounting journals (Önce & Başar, 2010;Şentürk & Fındık, 2014;Kıymetli Şen et al, 2017;Gündüz, 2018;Kuruçay & Serçemeli, 2018;Özbek & Badem, 2018;Temelli & Karcıoğlu, 2018;Dinç & Cengiz, 2019;Çarıkçı & Yaman, 2019;Güleç & Öztürk, 2019;Altunay, 2021b).…”
Section: Bulgularmentioning
confidence: 99%
“…The matter of improving performance has received the attention of accountants, as improving the financial performance of companies can be a done through the independence of the audit committees, and a study conducted in Tunisia in 2007-2010 found that the independence of the audit committees affects the rate of return on investment and thus leads to improved performance (Al-khoury et al, 2022).…”
Section: Concept Of Excellence In Financial Performancementioning
confidence: 99%